(untitled) (The Research of Medical Science Review, 2025)
Background: Maxillary sinusitis appears frequently as a medical problem but affects daily life badly. Doctors provide different surgical choices such as cleaning the sinus cavity and making an opening in the inferior meatus. Objectives: Our research evaluated which of these operations provided better benefits and reduced side effects for subacute and chronic maxillofemoral sinusitis patients. Methods: A 6-month ENT study at Nishtar Hospital Multan chose participants at random for selection. Research assigned 70 participants into two groups containing 35 patients each for antral washout and inferior meatal antrostomy studies. The study selected patients between 18 and 60 years old who had subacute or chronic maxillary sinusitis for participation. We assessed physical symptoms through the Visual Analog Scale at both start and end of the treatment while following patients for 6 months to monitor if symptoms returned. Our analysis depended on testing paired t-statistics and chi-square differences with Kaplan-Meier survival methods. Results: Each method led to major improvements in patient symptoms including lower pain ratings on their faces plus nose and head. The antral washout group reported somewhat more pain relief in both the nose and face but not enough to show significant effects. The repeat guidelines revealed 8.57% successful outcomes for antral washout but only 20% for inferior meatal antrostomy methods showing no statistical difference (p=0.23). The operations led to few problems with no notable differences between groups. The patients expressed similar satisfaction levels across both treatment groups because 90% in the first group and 85% in the second group rated their treatment experience positively. Conclusion: The surgery of antral washout delivers similar results to inferior meatal antrostomy for subacute and chronic maxillary sinusitis without major differences in patient feedback or illness return. More evidence from bigger research is required to validate the results showing antral washout benefits in easing symptoms and reducing return issues.